2016
DOI: 10.1093/gerona/glw128
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels and the Risk of Cognitive Decline in Chinese Elderly People: the Chinese Longitudinal Healthy Longevity Survey

Abstract: This first follow-up study of elderly people, including the oldest-old, in Asia shows that low vitamin D levels were associated with increased risk of subsequent cognitive decline and impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 41 publications
2
32
0
1
Order By: Relevance
“…5,7,8,16,27,[36][37][38][39][40][41] Eight studies reported vitamin D as a continuous variable, 5,6,10,27,29,36,39,42 27 as a categorical variable, and three reported both. Seventeen studies used a-priori cut offs 6,8,[14][15][16]28,34,35,37,41,[43][44][45][46][47][48][49] and 13 categorized into tertiles, 9,17,38,50,51 quartiles, 7,12,18,33 or quintiles. 13,40,52,53 The majority of studies analyzed serum 25OHD with four analyzing plasma 25OHD.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…5,7,8,16,27,[36][37][38][39][40][41] Eight studies reported vitamin D as a continuous variable, 5,6,10,27,29,36,39,42 27 as a categorical variable, and three reported both. Seventeen studies used a-priori cut offs 6,8,[14][15][16]28,34,35,37,41,[43][44][45][46][47][48][49] and 13 categorized into tertiles, 9,17,38,50,51 quartiles, 7,12,18,33 or quintiles. 13,40,52,53 The majority of studies analyzed serum 25OHD with four analyzing plasma 25OHD.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…13,40,52,53 The majority of studies analyzed serum 25OHD with four analyzing plasma 25OHD. 12,13,29,47 The most commonly reported vitamin D assays were the Dia Sorin radioimmune (n = 12) and liquid chromatography-tandem mass spectrometry (n = 10).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…60 Comparable findings were reported in China, where individuals with lower baseline vitamin D were 2 to 3 times more likely to have significant cognitive decline within 2 years compared to those with adequate levels. 61 …”
Section: Increased and Accelerated Cognitive Declinementioning
confidence: 99%